Purity is a myth : the materiality of concrete art from Argentina, Brazil, and Uruguay - Gilbert, Zanna, 1980-; Gottschaller, Pia; Learner, Tom; Perchuk, Andrew (Issues & debates., 2021)
"Purity Is a Myth presents new scholarship on Concrete art in Argentina, Brazil, and Uruguay from the 1940s to the 1960s"--